"Uncivilized children" or "victims of dementia": Interpretations of aggression in older assisted living tenants. (14th December 2021) - Saj, Danielle; Funk, Laura M.; Gerbrandt, Emily; Spencer, Dale; Herron, Rachel
Abstract: This study explores interpretations of interpersonal aggression involving older adults, through an analysis of semi‐structured interview data from 13 assisted living (AL) tenants and 19 AL service and/or care workers. Differing relations (tenant‐tenant and tenant‐worker) shape the kinds of tenant actions experienced as problematic and/or aggressive. Tenants and workers invoke communal living, aging, and dementia as explanatory frames, in part to mitigate victimization experiences through normalization and neutralization. This was more prominent among workers, who are less able to enact empowering responses as they sought to keep working in difficult circumstances. Structural constraints, and the power and social hierarchies that contribute to victimization, generate interpretive responses that obscure fulsome and contextualized understandings of the problem while further reinforcing oppressive discourses including a sense of the inevitability of aggression in older adults–especially those living with dementia. RÉSUMÉ: Cette étude explore les interprétations de l'agression interpersonnelle impliquant des adultes plus âgés, à travers une analyse des données d'entretiens semi‐structurés de 13 locataires de résidences assistées (RA) et de 19 travailleurs de services et/ou de soins RA. Des relations différentes (locataire‐locataire et locataire‐travailleur) façonnent les types d'actions des locataires vécues comme problématiques et/ou agressives. Les locataires et les travailleurs invoquent la vie en communauté, le vieillissement et la démence comme cadres explicatifs, en partie pour atténuer les expériences de victimisation par la normalisation et la neutralisation. Ce phénomène est plus marqué chez les travailleurs, qui sont moins à même d'adopter des réponses autonomisantes lorsqu'ils cherchent à continuer à travailler dans des circonstances difficiles. Les contraintes structurelles, ainsi que le pouvoir et les hiérarchies sociales qui contribuent à la victimisation, génèrent des réponses interprétatives qui obscurcissent les compréhensions complètes et contextualisées du problème tout en renforçant les discours oppressifs, y compris le sentiment de l'inévitabilité de l'agression chez les personnes âgées ‐ en particulier celles qui vivent avec la démence.